2019
DOI: 10.1007/s10973-019-08713-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamics (MHD) stagnation point flow past a shrinking/stretching surface with double stratification effect in a porous medium

Abstract: The present work emphasizes the MHD mixed convective stagnation point flow over a shrinking/stretching surface saturated in a porous medium. The double stratification with heat source effects are also considered while the magnetic field is imposed normal to the sheet. The governing model (partial differential equations) is converted into a system of ordinary (similarity) differential equations using similarity transformations. The boundary value problem solver (bvp4c) in the MATLAB software is utilized for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 50 publications
3
26
1
Order By: Relevance
“…The appearance of dual solutions were noticed with the imposition of suction parameter. Unlike Khashi’ie et al [ 26 ], the nanoliquid temperature and concentration profiles slightly inclined with the increment of thermal and solutal stratification parameters, respectively. This might be due to the application of strong suction and nanoparticles.…”
Section: Introductioncontrasting
confidence: 68%
See 2 more Smart Citations
“…The appearance of dual solutions were noticed with the imposition of suction parameter. Unlike Khashi’ie et al [ 26 ], the nanoliquid temperature and concentration profiles slightly inclined with the increment of thermal and solutal stratification parameters, respectively. This might be due to the application of strong suction and nanoparticles.…”
Section: Introductioncontrasting
confidence: 68%
“…The first (upper branch) solution is denoted for the first solution which satisfies the far field boundary condition. The current studies that discussed the stability formulation and analysis were reported by Khashi’ie et al [ 26 , 27 ], Bakar et al [ 36 , 37 ], Yahaya et al [ 38 ], Salleh et al [ 39 , 40 ] and Jamaluddin et al [ 41 ]. Additionally, the stability formulation for micropolar fluid flow towards a stretching/shrinking surface was recently reported by Soid et al [ 13 ] and Lok et al [ 42 ].…”
Section: Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…According to Haris et al [38] and Khashi'ie et al [39], one boundary condition has to be relaxed in order to obtain the value(s) of the smallest eigenvalue. It should be noted that this relaxation in boundary condition does not affect the results [40].…”
Section: Stability Analysismentioning
confidence: 99%
“…Simultaneous illustration of Jeffrey fluid with thermally radiated and thermally stratified medium via an extended surface is investigated by Hayat et al [ 37 ]. Some more observations about the research thermal and solutal stratification under different perspectives can be found at [ 38 , 39 , 40 , 41 , 42 , 43 ] many therein.…”
Section: Introductionmentioning
confidence: 99%